Magnetic [n × n] (n = 2−5) Grids by Directed Self-Assembly - Dawe, Louise N; Shuvaev, Konstantin V; Thompson, Laurence K (Inorganic chemistry, 2009)
Polytopic hydrazone-based ligands are discussed in the context of the design attributes of the ligand and the power of self-assembly as a methodology for the synthesis of polymetallic systems with specific and predetermined organization of the metal centers in a closely spaced bridged arrangement. Magnetic exchange coupling occurs as a result of the close proximity of the metal ions. Homometallic, heterometallic, and mixed-spin-state [n × n] (n = 2−5) square grids are highlighted and discussed in terms of their structural and magnetic properties. Antiferromagnetic, ferromagnetic, and ferrimagnetic examples are described.